2014
DOI: 10.1369/0022155413520607
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Subcellular Localization of Tektin2-Binding Protein 1 (Ccdc 172) in Rat Spermatozoa

Abstract: SummaryTektins (TEKTs) are composed of a family of filament-forming proteins localized in cilia and flagella. Five types of mammalian TEKTs have been reported, all of which have been verified to be present in sperm flagella. TEKT2, which is indispensable for sperm structure, mobility, and fertilization, was present at the periphery of the outer dense fiber (ODF) in the sperm flagella. By yeast two-hybrid screening, we intended to isolate flagellar proteins that could interact with TEKT2, which resulted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…It functions in the maintenance of sperm structures and movement [35]. ODF could be consider as a marker of male infertility factor and defects of ODF can lead to abnormal morphology and infertility [36].…”
Section: Discussionmentioning
confidence: 99%
“…It functions in the maintenance of sperm structures and movement [35]. ODF could be consider as a marker of male infertility factor and defects of ODF can lead to abnormal morphology and infertility [36].…”
Section: Discussionmentioning
confidence: 99%
“…TEKT2-null sperm exhibited flagella bending and reduced motility []). Recently, Yamaguchi et al [54] identified a 36kDa TEKT2-binding protein1 associated with mitochondria of rat sperm flagella. It has been reported that Tektin 2 of hamster sperm becomes tyrosine phosphorylated during in vitro capacitation [55].…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of the ODF major components (ODF1, ODF2, ODF3, and ODF4) were generally low in abundance in asthenozoospermatic men (Zhao et al, 2018). Thus, ODFs are involved in maintaining spermatozoa structure and movement (Yamaguchi et al, 2014). The absence of ODFs results in non-functional tails and affects spermatozoa motility (Yuan, 2014).…”
Section: Effect Of Vitrification On Outer Dense Fibers and Vimentinmentioning
confidence: 99%